Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Jasa Transportasi Online Maxim di Kota Palembang - Ruwananda, M.Edwin; Nailis, Welly (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Service Quality on Customer Satisfaction of online transportation services in Palemang City. The research method used is a quantitative method with a type of comparative causal research. The data used in the study are primary and secondary data. The sampling technique uses puruposive sampling technique. This study used a sample of 100 respondents who were people living in Palembang City. The data analysis used is by F test, T test, and multiple linear analysis. The results of test F show that the variable of service quality simultaneously affects the satisfaction of Maxim customers in Palembang City.